Always-best-served music distribution for nomadic users over heterogeneous networks. - Ghini, Vittorio (IEEE Communications magazine)
The distribution of online music has played a key role in driving the digital multimedia entertainment business to the pervasive extent we know today. The digital music revolution was substantially fueled by the invention of new online distribution models, such as P2P file sharing and online music libraries containing over one million songs in a pay-per-listen fashion. In this context, a new generation of devices that seamlessly integrate multiple radio access technologies is quickly emerging into a market for handheld devices. These devices contributes to the spread of ubiquitous multimedia for everywhere entertainment, and also strongly influence music consumer habits. New music distribution models be implemented to offer the user mobile services based on integrated wired/wireless infrastructures. Novel services allows users to establish or negotiate a music download considering a complex set of access selection criteria, thereby accessing music in the best possible way. The user, moving from a music shower that distributes digital music contents to a 3G wireless entry point, could also decide to nomadically change the download and playout device. An individual who is entering a car while downloading through a cell phone continues the download using the car radio, and finally end the file transfer on a home theatre. In this article we investigate the architectural requirements to effectively support a ubiquitous and nomadic multimedia entertainment service, and propose a music distribution system that offers a seamless and wandering music delivery service. We present experimental results that show the functionalities and performances of our proposed approach in terms of reliability and effectiveness.